Efficacy of phacoemulsification combined with goniosynechialysis for primary angle closure glaucoma - I. Ia. Novytskyy; R. M. Lopadchak; M. I. Novytskyy (Ukrainian Society of Ophthalmologists, 2020)
Background: To date, no universal surgical strategy exists for primary angle closure glaucoma (PACG). Purpose: To assess the clinical efficacy and hypotensive effect of phacoemulsification (phaco) combined with goniosynechialysis (GSL) for the treatment of PACG. Material and Methods: Nine patients (9 eyes; mean age, 63.4 ± 9.6 years) with chronic angle-closure glaucoma who were under our observation were included in this study. Of these, 8 (8 eyes) underwent phaco-GSL, and one (1 eye) underwent GSL at some time after phaco. Failure to control IOP (the IOP higher than 22 mmHg on maximal tolerable hypotensive therapy) and synechial closure of the anterior chamber angle was the indication for surgery. Results: Using the Mori goniolens was helpful in performing GSL in all anterior chamber quadrants. The IOP was 26.33 ± 3.6 mmHg before surgery, 18.44 ± 0.88 mmHg on day 7, 18.44 ± 1.13 mmHg on day 30, and 18.11 ± 1.5 mmHg on day 90. Visual acuity improved from 0.09 ± 0.05 to 0.35 ± 0.2. Mean number of hypotensive medications decreased from 2.8 ± 0.92 pre-surgery to 0.77 ± 0.83 post-surgery. Conclusion: Phacoemulsification in combination with GSL has a good hypotensive effect. Intraoperative visualization of the anterior chamber angle and transection of synechia in all quadrants allows improving the efficacy of GSL procedure.